Dissolved organic matter and sulfide enhance the CH4 consumption of a psychrophilic lake methanotroph, Methylobacter sp. S3L5C - Rissanen, Antti Juhani; Mangayil, Rahul; Tveit, Alexander T.; Maanoja, Susanna T.; Khanongnuch, Ramita (American Society for Microbiology, 2025)
Gammaproteobacterial methanotrophic bacteria (gMOB) are dominant methanotrophs in the water column of oxygen-stratified boreal and subarctic lakes and ponds. (Meta)genomic data suggest that, besides methane (CH4), gMOB potentially use dissolved organic matter (DOM) and reduced sulfur compounds (e.g., sulfide) as electron sources. To study the DOM and sulfide metabolism of lake gMOB, we subjected a psychrophilic lake water strain, Methylobacter sp. S3L5C, first to different sulfide levels (Na2S, 0–5 mM) to test the toxicity, and subsequently, to freshwater DOM (60 mg L−1) either alone or with sulfide (0.05 mM) at 1 and 20% CH4 levels. The growth, CH4 and O2 consumption, CO2 production, and mRNA expression patterns of S3L5C were analyzed. Sulfide concentrations of 0–0.5 mM had no effect, while 1 and 5 mM concentrations inhibited the strain’s growth. At 20% CH4, DOM addition enhanced CH4 consumption, CO2 production, and growth of S3L5C, while the addition of sulfide+DOM led to further increases in these variables. The addition of sulfide+DOM enhanced CH4 consumption even at 1% CH4. The effect of DOM on the S3L5C’s metabolism was accompanied by enhanced expression of the cyc2 gene, which has been suggested to mediate the extracellular electron transfer from DOM. Furthermore, the addition of sulfide+DOM enhanced the expression of the sqr and soxB genes encoding dissimilatory sulfide and thiosulfate oxidation, respectively. Together with previous metagenomic data, these results suggest that the usage of DOM and reduced sulfur compounds as electron sources is a trait that enhances methanotrophy among gMOB of boreal and subarctic lakes and ponds.
Keywords: methanotroph; methane oxidation; Methylobacter; lake; pond; greenhouse gas; extracellular electron transfer; dissolved organic matter; sulfide